GREEN CAMPUS INITIATIVE: TRANSFORMING LAW IN BOOK INTO LAW IN ACTION - Rina Shahriyani Shahrullah; Agustina Fitrianingrum; R.A. Widyanti Diah Lestari (Fakultas Hukum Universitas Gadjah Mada, 2014)
Global warming has become a serious threat to our earth today. To overcome the problems of global warming, various parties should get involved including campus community (students, staff and faculty members). The participation of tertiary education institutions in minimizing global warming is referred to as ‘green campus initiative’ (GCI). This participation is mandated by Law No.32 of 2009 on Environmental Protection and Management. This paper suggests the adoption of GCI and provides a GCI model for Indonesian higher education institutions. This paper also discusses the GCI activities which can be adopted either by small or big campuses in Indonesia. Pemanasan global telah menjadi ancaman serius bagi bumi kita dewasa ini. Untuk mengatasi masalah pemanasan global, berbagai pihak telah terlibat termasuk komunitas kampus (mahasiswa, karyawan dan dosen). Partisipasi perguruan tinggi dalam meminimalkan pemanasan global dinamakan ‘green campus initiative (GCI)’. Partisipasi ini diamanatkan oleh Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup. Makalah ini menyarankan penerapan GCI dan memberikan Model GCI untuk perguruan tinggi di Indonesia. Makalah ini juga membahas kegiatan-kegiatan GCI yang dapat digunakan baik oleh kampus kecil maupun besar di Indonesia